Detecting and understanding the accelerated sea level rise along the east coast of the United States during recent decades. Issue 12 (18th December 2014) - Kenigson, J. S.; Han, W.
Abstract A "hot spot" of accelerated sea level rise has recently been detected between Cape Hatteras and Cape Cod. The acceleration in the long‐term trend, however, is difficult to isolate from transient acceleration due to variability, particularly the ∼60 year cycle associated with the Atlantic Multidecadal Oscillation (AMO). The Empirical Mode Decomposition (EMD) and Ensemble EMD (EEMD) methods have been used to isolate oscillations and provide robust acceleration estimates for the trend. Yet the reliability of these methods in detecting accelerated sea level rise, particularly given the limited lengths of tide gauge records, has not been fully tested. Here, the EMD and EEMD methods are applied to both tide gauge observations and synthetic sea level time series constructed as a sum of oscillations extracted from tide gauge records and trends with prescribed acceleration rates. The successively truncated synthetic and observed data are analyzed with (E)EMD, and estimates of the acceleration error based on the record length are produced. Generally, EEMD provides more stable acceleration estimates than EMD, and the error decreases as the record length increases, although not monotonically. Records exceeding two multidecadal oscillation periods in length provide superior estimates over shorter records. In addition, the AMO may have contributed significantly to the rapid acceleration detected in the hot spot during recent decades. These findings have important implications for improved detection of regional sea level acceleration in a warming climate.